THE INFLUENCE OF ORGANIC SOLVENT PROTEIN PRECIPITATION ON SDS PAGE PROTEIN PROFILE IN SERUM - Tri Joko Raharjo; Rusmiati Suprihatin; Deni Pranowo (Indonesian Journal of Chemistry, 2007)
A study on the influence of organic solvent protein precipitation to the profile of the serum protein has been accomplished. The expected conditions were precipitation of abundant proteins present in serum result in increasing relative concentration of minor protein which can be useful for sample preparation for biomarker studies. The serum were precipitated with various diluted (<10%) acetonitrile, methanol and ethanol followed by SDS-PAGE analysis of the supernatant in order to investigate the protein profile. There were no linear relationship between solvent concentration and the number of protein bands. However, an optimal condition of precipitation was found which is by methanol 0.1%.